Two new triterpenoids from the leaves of Cyclocarya paliurus (Batalin) Iljinskaja. Issue 15 (1st August 2022) - Liu, Yao; Zheng, Guan-Tao; Zhang, Xuan-Xuan; Zhang, Xian-Tao; Shang, Xu-Lan; Fang, Sheng-Zuo; Zhang, Jian; Yin, Zhi-Qi
Abstract: Two previously undescribed triterpenoids (1–2 ), along with thirteen known compounds (3–15 ) were isolated from a CHCl3 -soluble extract of the leaves of Cyclocarya paliurus . Their structures were established on the basis of chemical and spectroscopic approaches. These compounds were assessed for their therapeutic effects on diabetic nephropathy (DN)-evoked fibrosis through High-Glucose and transforming growth factor-β1 (TGF-β1) challenged HK-2 cells. Among them, compounds 3, 5 and 8 could remarkedly decrease the level of fibronectin to relieve DN with 27.66 ± 2.77%, 6.09 ± 0.57% and 17.74 ± 5.83% inhibition rate at 10 μM, 10 μM and 1 μM, respectively. Graphical Abstract: UF0001